2017
DOI: 10.1002/mgg3.354
|View full text |Cite
|
Sign up to set email alerts
|

Genetic testing including targeted gene panel in a diverse clinical population of children with autism spectrum disorder: Findings and implications

Abstract: BackgroundGenetic testing of children with autism spectrum disorder (ASD) is now standard in the clinical setting, with American College of Medical Genetics and Genomics (ACMGG) guidelines recommending microarray for all children, fragile X testing for boys and additional gene sequencing, including PTEN and MECP2, in appropriate patients. Increasingly, testing utilizing high throughput sequencing, including gene panels and whole exome sequencing, are offered as well.MethodsWe performed genetic testing includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 56 publications
3
22
1
2
Order By: Relevance
“…Moreover, they found 38 proteins related to cognitive trajectory independently of β-amyloid plaques and neurofibrillary tangles [ 52 ]. Studies conducted on non-neurological tissues highlighted changes in quantities of proteins associated with inflammation or regulation of the immune system, including some interleukins [ 50 , 51 , 105 , 106 , 107 , 108 ]. Interestingly, most proteomic studies investigating ASD identified proteins involved in lipid metabolism and differentially expressed in ASD [ 51 , 55 , 57 , 105 , 106 , 109 , 110 ].…”
Section: Translational and Clinical Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they found 38 proteins related to cognitive trajectory independently of β-amyloid plaques and neurofibrillary tangles [ 52 ]. Studies conducted on non-neurological tissues highlighted changes in quantities of proteins associated with inflammation or regulation of the immune system, including some interleukins [ 50 , 51 , 105 , 106 , 107 , 108 ]. Interestingly, most proteomic studies investigating ASD identified proteins involved in lipid metabolism and differentially expressed in ASD [ 51 , 55 , 57 , 105 , 106 , 109 , 110 ].…”
Section: Translational and Clinical Proteomicsmentioning
confidence: 99%
“…Studies conducted on non-neurological tissues highlighted changes in quantities of proteins associated with inflammation or regulation of the immune system, including some interleukins [ 50 , 51 , 105 , 106 , 107 , 108 ]. Interestingly, most proteomic studies investigating ASD identified proteins involved in lipid metabolism and differentially expressed in ASD [ 51 , 55 , 57 , 105 , 106 , 109 , 110 ]. As an example, Corbett et al identified differentially expressed peptides using LC-MS/MS, which allowed for the recognition of complement factor H-related protein (FHR1), apolipoprotein (APO) B-100, fibronectin 1 (FN1), and complement C1q as dysregulated proteins in children with ASD compared to control subjects [ 53 ].…”
Section: Translational and Clinical Proteomicsmentioning
confidence: 99%
“…These techniques have impacted every field of molecular research, escalating previously used sequencing technologies [ 11 ], and opening the way to the -omic sciences foundation [ 1 , 2 ]. Indeed, NGS methods allow the sequencing of entire genomes [ 12 , 13 , 14 , 15 ], of exomes [ 16 , 17 , 18 ], of panels of genes related to a disease of interest [ 19 , 20 , 21 ], or of a single gene [ 22 , 23 , 24 , 25 , 26 ], but can also be used to explore the entire transcriptome [ 27 , 28 , 29 ], small RNAs [ 30 , 31 , 32 ], the epigenome [ 33 , 34 ], and the microbiome [ 35 , 36 , 37 , 38 ].…”
Section: High-throughput Analysesmentioning
confidence: 99%
“…In this view, it is not surprising that NGS is also becoming a reference method for molecular diagnostics [ 10 ]. In particular, NGS allows not only the analysis, in more patients simultaneously, of disease-related genes in less time and at lower costs than traditional approaches, but also the sequencing of panels of genes up to the complete exome [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. In this way, it is possible to increase the diagnostic sensitivity, to discover novel disease-related genes and also obtain data regarding other genes that were potentially acting as disease-phenotype modifiers [ 19 , 40 , 41 , 42 ].…”
Section: High-throughput Analysesmentioning
confidence: 99%
“…Typical examples include extreme presentations of obesity, short or tall stature, and autism spectrum disorders . However, in most cases, children with such phenotypic presentations investigated with targeted gene panels are found to be negative for mutations in known disease‐related genes . Although such cases could still be caused by Mendelian mutations in unknown genes, it is also possible that such patients have an increased burden of common risk alleles, which individually confer a small risk of disease but taken together can have large effects on disease risk .…”
Section: Introductionmentioning
confidence: 99%